2015
DOI: 10.1021/ac504752a
|View full text |Cite
|
Sign up to set email alerts
|

Long-Circulating Iodinated Albumin–Gadolinium Nanoparticles as Enhanced Magnetic Resonance and Computed Tomography Imaging Probes for Osteosarcoma Visualization

Abstract: Multimodal imaging probes represent an extraordinary tool for accurate diagnosis of diseases due to the complementary advantages of multiple imaging modalities. The purpose of the work was to fabricate a simple dual-modality MR/CT probe for osteosarcoma visualization in vivo. Protein-directed synthesis methods offer a suitable alternative to MR/CT probe produced by synthetic chemistry. Bovine serum albumin (BSA) bound to gadolinium nanoparticles (GdNPs) was first prepared via a biomimetic synthesis method and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
39
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 44 publications
(39 citation statements)
references
References 30 publications
0
39
0
Order By: Relevance
“…The T 1 ‐weighted mapping exhibited Gd concentration‐dependent brightness of high contrast with a longitudinal relaxation rate ( r 1 ) of 13.75 m m −1 s −1 , indicating an evident increase as compared to that of Gd‐DTPA (3.63 m m −1 s −1 ) (Figure S8, Supporting Information). Noteworthily, PIGH NPs exhibited stronger signals than the clinical contrast agent (Gd‐DTPA), which might result from the formation of Gd 2 O 3 nanocrystals in PIGH NPs with relatively suitable size …”
Section: Resultsmentioning
confidence: 99%
“…The T 1 ‐weighted mapping exhibited Gd concentration‐dependent brightness of high contrast with a longitudinal relaxation rate ( r 1 ) of 13.75 m m −1 s −1 , indicating an evident increase as compared to that of Gd‐DTPA (3.63 m m −1 s −1 ) (Figure S8, Supporting Information). Noteworthily, PIGH NPs exhibited stronger signals than the clinical contrast agent (Gd‐DTPA), which might result from the formation of Gd 2 O 3 nanocrystals in PIGH NPs with relatively suitable size …”
Section: Resultsmentioning
confidence: 99%
“…CT investigation shows that nanoparticles have a significant attenuation effect with increasing densities; MRI investigation shows that nanoparticles have higher r weighting value than commercially available Ferumoxtran‐10 (Sinerem) contrast agent and almost equal to Endorem. Further studies for Gd nanoparticles as MRI/CT dual modeling agent were reported by Wang et al () and Zheng et al (). Wang coated the Gd nanoparticles with bovine serum albumin (BSA) and functionalized the coating with iodine that spheric monodisperse 2.5 ± 0.3 nm I‐BSA‐Gd nanoparticles were obtained with excellent stability with high magnetic resonance.…”
Section: Nanoparticle‐based Staining Agentsmentioning
confidence: 95%
“…Fortunately, the development and application of molecular imaging technologies in biomedicine for theranostics enable precise real-time IGS. [213] I-BSA-GdNPs demonstrated a long circulating time as the enhanced MRI/CT signals lasted over 24 h after intravenous injection. Therefore, CT, MRI, and PET/SPECT are still the major preoperative imaging methods for most cancer patients.…”
Section: Preoperative Imaging For Precision Surgerymentioning
confidence: 99%